Observation on Therapeutic Effect of Neuromuscular Electrical Stimulation and Rehabilitation Training on Dysphagia Patients Caused by Different Brain Injuries and Effect on Their Hyoid Motion - Yan LI (康复学报)
Objective:To observe the clinical curative effect of neuromuscular electrical stimulation (NMES) and rehabilitation training on dysphagia patients caused by different brain injuries, and explore the influence of hyoid motion due to different electrode placement positions.Methods:A total of 55 dysphagia patients with different brain injuries were assigned to four groups according to the type of brain injuries. There were 17 dysphagia patients due to brain tumor oppression of nerve were recruited in group A, 14 dysphagia patients due to cerebral thrombosis were recruited in group B, 14 dysphagia patients due to parkinsonian syndrome were recruited in group C, and 10 dysphagia patients due to cerebral palsy were recruited in group D. All patients received NMES and rehabilitation training. Two protocols with different electrode placement positions were applied, one with the electrode placed in submental area and throat area (E method), and the other one with two electrode placed in submental area (F method). All patients received two protocols respectively by cross control design. When the patients received the first protocol, were treated with NMES for two weeks, twenty minutes each time, ten times a week, then the swallowing function changes of all four groups were observed. After washing for one month, all patients received the second protocol with the same course. The functional oral intake scale (FOIS) and dysphagia outcome severity scale (DOSS) were used to assess swallowing function and swallowing visualization was used to observe hyoid motion.Results:After treatment, the FOIS scores and DOSS scores in all four groups were increased significantly (P<0.05). After received two protocols of different electrode placement positions, respectively, the vertical lift amplitude and forward movement range of hyoid bone of patients were both improved (P<0.05). The effect of E protocol was better than F protocol on vertical lift amplitude, but the effect of F protocol was better than E protocol on forward movement range.Conclusion:NMES and rehabilitation training can improve dysphagia caused by different brain injuries. Choosing electrode stimulating site according to the hyoid motion of patients could improve swallowing function effectively.